Facing the challenges of using place-based social-ecological research to support ecosystem service governance at multiple scales. Issue 1 (1st January 2021) - Bennett, E. M.; Morrison, P.; Holzer, J. M.; Winkler, K. J.; Fraser, E. D. G.; Green, S. J.; Robinson, B. E.; Sherren, K.; Botzas-Coluni, J.; Palen, W.
ABSTRACT: Place-based social-ecological research is often designed to improve local environmental governance, but it can also inform decisions at larger scales or in other places. However, the focus on local perspectives in such research creates challenges for transferring insights to other locations, and for aggregating understanding to larger scales. In this paper, we discuss how ResNet, a new pan-Canadian network of researchers working on place-based social-ecological case studies via ecosystem services, will face (and hopefully overcome) these challenges while taking advantage of the unique benefits of a place-based approach. Drawing on insights from the literature and from the first 10 years of the Programme for Ecosystem Change and Society (PECS), we outline solutions to six key challenges to multi-scale knowledge integration across place-based cases, and explore how ResNet is employing some of these solutions.